2016
DOI: 10.1016/j.livsci.2016.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of pulmonary arterial pressure and terrain use of Angus cows grazing high-altitude foothill rangelands

Abstract: Pulmonary arterial pressure (PAP) score is used as an indicator trait for risk of 20 hypoxia-induced pulmonary hypertension, which is commonly termed high altitude disease and 21 observed in cattle grazing at altitude ≥ 1500 m. We hypothesized that cows with higher PAP 22 score would avoid using high elevations, steep slopes and areas far from water while grazing 23 foothill rangeland. During 2013 and 2014, forty-one mature Angus cows from a breeding 24 population of cattle selected for tolerance to high altit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
1
1
Order By: Relevance
“…Furthermore a significant difference among Muturu and Sokoto gudali on the total grazing record which contradict the findings of this study has been reported [24]. Muturu is highly adapted breed in southern part of Nigerian while Sokoto gudali in northern part of Nigeria, his experiment was undertaken in south east of the country recalling that grazing behavior can be acquired [25] and has been repeatedly reported to be affected by geographical condition.…”
Section: Parameterscontrasting
confidence: 90%
“…Furthermore a significant difference among Muturu and Sokoto gudali on the total grazing record which contradict the findings of this study has been reported [24]. Muturu is highly adapted breed in southern part of Nigerian while Sokoto gudali in northern part of Nigeria, his experiment was undertaken in south east of the country recalling that grazing behavior can be acquired [25] and has been repeatedly reported to be affected by geographical condition.…”
Section: Parameterscontrasting
confidence: 90%
“…Cows differing in their phenotypical habit to use hilly terrains graze different parts of the same pasture; “hill climbers” use rougher terrain and begin travelling to water about one hour later than cows previously classified as “bottom dwellers” [ 88 ], showing the degree of asynchrony in the motivation to eat or drink of different individuals [ 37 ]. However, other phenotypical traits (e.g., differences in pulmonary arterial pressure) between “hill climbers” or “bottom dwellers”, are not useful predictors of terrain preference within Angus cows adapted to high elevations [ 89 ].…”
Section: Effect Of Animal Factors and Social Interactions On Site Use Preferencementioning
confidence: 99%